True Cost Accounting and Social Entrepreneurship as Key Factors for a New Food System - Ortega Moreno, Irma Cecilia; Galicia Haro, Emma Frida; Coria Páez, Ana Lilia (Mercados y Negocios, 2023)
The paper aims to understand the problems of the food system, identify the value of food, and the role of social entrepreneurs in changing the status quo. Based on this objective, this documentary and descriptive work present a first approach to understanding the food system, and the search for solutions to measure the value of food and its key actors. The methodology was a documentary search on the world food crisis, true cost accounting, and social entrepreneurship[i]. [i] This document was carried out with resources from the project "Analysis of market options for a planned development of social enterprises with food security innovation" with registration SIP 20222098.